Semblanza y liderazgo de Omar Dengo: vigencia de su pensamiento - Alfaro Rodríguez, Magdalena (2009)
Aspects of the life of Omar Dengo outline and define him as a figure of outstanding humanistic leadership. His pedagogical work and social commitment are reflected in his actions for civilian causes, which transcend his times and continue to be valid today.